Effects of Mindfulness-Based Practices on Children’s Self-Regulation: A Review on Early Childhood Research - Aylin SOP; Buse HANÇER (Hayef: Journal of Education)
In studies conducted on the early childhood years in recent years, there has been an increase in the number of mindfulness-based practces in the development of mental and physical health. Mindfulness is used to develop awareness-related skills such as atenton, concentraton, emoton regulaton, and metacogniton that improve self-regulaton while children are aware of their experiences. In the current study, the literature was reviewed with 17 studies published between 2010 and 2022 on the efectveness of mindfulness in the self-regulaton skills of children aged 3–7. The reviewed studies were analyzed with the content analysis technique, and the fndings were presented in themes and codes. As a result of the research, 17 studies have demonstrated that mindfulness improves children’s self-regulaton skills and reduces negatve emotons and behavior. The studies have demonstrated that frequent use of mindfulness training in early childhood supports children’s skills such as positve social behavior, empathy, prosocial behavior, executve functon, and emoton management and is associated with higher levels of emoton, thought, and behavior regulaton skills. Considering the data obtained from the results, it benefts teachers and educators to make mindfulness-based programs common for children’s emoton, atenton, and behavior regulaton from an early age. Potental aspects for further research were also discussed.